Mediating Role of Artificial Intelligence to Impact Purchase Decisions - Martina, Dannia Ayu; Kurdaningsih, Dian Marhaeni; Trimanah, Trimanah (Program Studi Ilmu Komunikasi FBIK Unissula, 2025)
AbstractAlong with the development of digital technology, Artificial Intelligence (AI) plays a role as a mediator in understanding consumer preferences and behavior more deeply, so as to influence purchasing decisions. This study seeks to understand how AI can strengthen the relationship between consumer motivation and brand image with purchase decisions, which can provide new insights for companies in designing more effective and data-driven marketing strategies. Therefore, this study examines how AI as a technology can mediate the influence of consumer motivation and brand image on purchasing decisions for Garnier products. The type of research used is explanatory research using non-probability sampling with purposive sampling method, which allows sample selection based on certain criteria. Primary data was collected using a questionnaire distributed to respondents who met the research criteria. Furthermore, the collected data will be tested using the validity and reliability of the instrument, and analyzed using appropriate statistical techniques to test the relationship between variables. Based on the results of the t-test and Sobel test analysis, this study shows that all hypotheses proposed are proven significant. The t test indicates that consumer motivation and brand image have a significant effect on purchasing decisions and the use of AI Skin Coach. The Sobel test results reinforce these findings by showing that AI Skin Coach acts as a significant mediating variable in the relationship between consumer motivation and purchasing decisions. In addition, AI Skin Coach also acts as a significant mediating variable in the relationship between brand image and purchasing decisions. AbstrakArtificial Intelligence (AI) telah menjadi elemen penting dalam memahami perilaku konsumen dengan menyediakan wawasan berbasis data yang lebih mendalam. Penelitian ini mengeksplorasi peran AI sebagai mediator dalam hubungan antara motivasi konsumen sebagai aspek penting dalam psikologi konsumen, citra merek, dan keputusan pembelian dengan menggunakan Self-Determination Theory, Decision-Making Theory, Technology Acceptance Model (TAM), dan konsep Brand Image. Studi ini berfokus pada bagaimana AI dapat memperkuat pengaruh motivasi konsumen dan citra merek terhadap keputusan pembelian produk Garnier. Metode penelitian yang digunakan adalah penelitian eksplanatori dengan pendekatan non-probability sampling dan metode purposive sampling, di mana data primer dikumpulkan melalui kuesioner yang disebarkan kepada responden yang memenuhi kriteria penelitian. Data yang diperoleh dianalisis menggunakan uji validitas, reliabilitas, uji t, dan uji Sobel untuk menguji hubungan antar variabel. Hasil penelitian menunjukkan bahwa motivasi konsumen dan citra merek berpengaruh signifikan terhadap keputusan pembelian dan penggunaan AI Skin Coach. Selain itu, uji Sobel mengonfirmasi bahwa AI Skin Coach berperan sebagai mediator signifikan dalam hubungan antara motivasi konsumen serta citra merek terhadap keputusan pembelian. Temuan ini memberikan implikasi bahwa AI tidak hanya mendukung personalisasi strategi pemasaran, tetapi juga meningkatkan efektivitas pengambilan keputusan konsumen melalui data yang lebih akurat dan relevan.